Integrating Technology into Extensive Reading for Students of English Study Program - Rivi Antoni; Batdal Niati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Reading cannot be separated in University level. Reading can be defined as a compulsory subject which consists of Intensive Reading and Extensive Reading. These subjects must be completed in different level. Extensive reading is the way for students to develop their competencies. However, most of students do not read in English extensively. They do not read English book, magazine, and others to improve their competencies meanwhile they are English students. In case, their motivation and scores are low. However, the lecturer has to integrate technology to improve, motivate and support them to read extensively. This research was qualitative research. The interview was the instrument. Finding showed that students’ scores and motivation increase and they were accustomed to read extensively.